2014
DOI: 10.1039/c4ra10616d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene-like g-C3N4/Fe3O4 nanocomposites with high photocatalytic activity and applications in drug delivery

Abstract: Graphene-like g-C 3 N 4 nanosheet (GCN)/Fe 3 O 4 quantum dot (QD) nanocomposites were successfully synthesized by a facile electrostatic self-assembly method. Characterization shows that the GCN is at least several micrometers in size. The GCN/Fe 3 O 4 nanocomposites were used as photocatalysts for degradation of Rhodamine B (RhB) under visible light irradiation. After irradiation for 1.5 h, the degradation efficiency was 72.5% for pure g-C 3 N 4 , 81% for GCN-1 wt% Fe 3 O 4 , 95% for GCN-2 wt% Fe 3 O 4 , 60.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 46 publications
(47 reference statements)
2
23
0
Order By: Relevance
“…The thin silk-like structure of g-C 3 N 4 nanosheets could be readily observed in Fig. 4a, while the darker part in the image was the wrinkle or overlap of g-C 3 N 4 [31]. The diameter of CeO 2 nanoparticles was about 20nm (Fig.…”
Section: Characterization Of Structure and Morphologymentioning
confidence: 86%
“…The thin silk-like structure of g-C 3 N 4 nanosheets could be readily observed in Fig. 4a, while the darker part in the image was the wrinkle or overlap of g-C 3 N 4 [31]. The diameter of CeO 2 nanoparticles was about 20nm (Fig.…”
Section: Characterization Of Structure and Morphologymentioning
confidence: 86%
“…2D, or graphitic carbon nitride (C 3 N 4 ) is a relatively new material, having only been synthesized in the last couple of years . Ultrathin graphitic C 3 N 4 (g‐C 3 N 4 ) nanosheets were produced for the first time in 2012, and have been found to exhibit high intrinsic photoabsorption and photoresponsiveness, semiconductive properties, high stability under physiological conditions, and good in vitro biocompatibility . These properties lend the material to applications as an imaging agent, drug delivery vehicle, and in biosensing.…”
Section: Other Types Of 2d Nanomaterialsmentioning
confidence: 99%
“…Doxorubicin release was achieved via a pH‐responsive mechanism: increased hydrophilicity of doxorubicin at lower pHs caused it to dissociate from the nanocarrier. In another recent trial, ultrathin C 3 N 4 –Fe 3 O 4 nanocomposites were shown to have high photocatalytic efficiency . Carbon nitride nanosheets have also been shown to be an effective biosensor due to their semiconductive properties, fluorescence, and high stability under a wide variety of conditions.…”
Section: Other Types Of 2d Nanomaterialsmentioning
confidence: 99%
“…38 Several modications, such as chemical doping with metal and non-metals, have been attempted to improve the photocatalytic activity of pure g-C 3 N 4 . [39][40][41][42][43][44][45][46][47][48][49] On the other hand, ruthenium nanoparticles are known for their potential in various catalysis-based applications. [50][51][52][53][54][55][56] Because of their quantized nature, ruthenium nanoparticles can enhance the efficiency of photo-excited electron-hole pair separation and thereby, increase the photocatalytic activity of nanocomposites comprising g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the separation of the catalyst can be made simpler by incorporating a magnetic support. 46,[59][60][61][62][63][64][65][66][67][68] A potentially efficient photocatalytic system would possess the combined advantages of g-C 3 N 4 , porous RuNP and magnetic Fe 3 O 4 NP. Considering this hypothesis, herein, we demonstrate the development of a ruthenium-based magnetic g-C 3 N 4 /Fe 3 O 4 /p-RuNP nanocomposite system and investigate its photocatalytic behaviour towards the decomposition of water-soluble aromatic amines and azo dyes from water bodies.…”
Section: Introductionmentioning
confidence: 99%